THE DEVELOPMENTAL PSYCHOLOGY OF ELEMENTARY SCHOOL STUDENTS: A LITERATURE REVIEW - Prananda, Gingga; Judijanto, Loso; Asiyah, Dewi; Cahyono, Didik; Aristanto, Aristanto; Salahuddin, Amar (Dharmas Education Journal (DE_Journal), 2024)
The aim of this research is to provide information about the developmental psychology of elementary school students. The type of research used in this research is library research, namely research carried out by collecting data or scientific writing aimed at research objects or library data collection, or research carried out to solve a problem which is basically focused on critical and in-depth review of relevant library materials. The data sources for this research are books, articles and websites related to the selected topic. The data source for this research consists of 30 references regarding the developmental psychology of elementary school students. The development phases of elementary school children are divided into 5 phases, namely, the prenatal phase (while in the womb), the infant phase, the early childhood phase, the late childhood phase and the adolescent phase. Estimated time is determined at each stage to obtain a time picture from the beginning to the end of the stage. Each individual child must go through a developmental phase, because behavior is formed as a reaction to growth given by both the family environment and the external environment. Therefore, parents or teachers need to collaborate to understand what should be given to children when going through the development phase so that children have psychological and physical readiness to develop their own potential